Technology literacy training for school-age children in anticipation of the Industry 4.0 era in Batuloceng Village, Suntenjaya, Lembang - Nurgianti, Sri Dewi Rahayu; Nabilah, Balqis Zahra; Rossa, Yustika; Oktafiani, O.; Azzahra, Salima (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2023)
Now we have entered the digital era, where every individual must be able to use technology well. In addition to daily needs, the education sector is one of the fields that require the use of technology. Suntenjaya Village, as a tourist village, has abundant natural wealth and beautiful scenery, so children often play in the open. The habit of children in Batuloceng Village is playing in the open. They rarely or never even operate computer devices and devices. This has a positive impact. Namely, children are not dependent on gadgets. Still, on the other hand, technology is also very much needed for their future careers. This community service activity aims to introduce computer technology (laptops) to children in Suntenjaya Village. This activity is one of the efforts to be literate in technology in the digital era. The method used is technology literacy training to empower the community. The result of this training was that there was an increase in the ability of children, who at first did not know how to operate a laptop and after the training knew how to turn on and off a computer, type in a word processing application, and surf the internet via a computer.